WAYS OF DEVELOPING ISLAMIC FINANCE IN UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
The development of Islamic finance has become an important trend in the global financial system due to its ethical principles, risk-sharing mechanisms, and contribution to sustainable economic growth. This study examines the prospects and challenges of developing Islamic finance in Uzbekistan.
Keywords: Islamic finance, Islamic banking, Shariah-compliant finance, financial inclusion, Sukuk, economic development, financial system, Islamic financial institutions, Uzbekistan, sustainable finance